FAKTOR PENYEBAB KESULITAN BELAJAR SISWA PADA MATA PELAJARAN IPS - man, Herman man (Makassar Journal of Social Sciences, 2013)
This study aims to determine what are the factors that cause learning difficulties students in social studies and what are the efforts that teachers in addressing students' learning difficulties in social studies subjects in SMP Negeri 4 Makassar. The type of research used in this research is qualitative research. While based on the sources and types of data in this study there are two , namely primary data and secondary data. The primary data obtained by researchers is the result of interviews with school principals, teachers Field of Social Studies, Teacher BK, and some students and IX5 VIII7 class, while secondary data obtained from the archives, as well as documents obtained by investigators. The data collection techniques in this study using the techniques of observation, interviews, and documentation, then dianilisis with qualitative descriptive technique.The results showed that the factors that cause learning difficulties students in social studies subjects in SMP 4 Makassar is the internal factors and external factors. Internal factors include sick / unhealthy body, talents, interests, and motivations. While external factors include teachers, factors equipment / facilities, a school and a lack of discipline, as well as the factor of mass media and social environment. Of several factors that are found in the field, the most dominant factors that cause learning difficulties students in social studies originated from the students themselves are factors of interest, and the efforts of teachers in addressing students' learning difficulties in social studies subjects in SMP 4 Makassar is the selection of appropriate learning methods, providing training in the form of homework, increase student interest, and to cooperate with the school and engage with the parents.